TANDA VERBAL DAN VISUAL DALAM VIDEO KLIP DOUSHITE KIMI WO SUKI NI NATTE SHIMATTAN DAROU DAN STAND BY U - Sriumiyanti, Putu Ika (Humanis; Volume 7. No. 1. April 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This Thesis entitled Verbal and Visual Sign in Doushite Kimi Wo Suki Ni Natte Shimattan Darou and Stand By U Music Video . The collection data method and technique used in this study is a seeing, listening method and note taking technique . The analysis method used in this study is a qualitative analysis with selection technique, and presentation of data analysis results used informal methods with inductive technique. This research is aimed at describing the element visual communication and the relation between verbal and visual sign in Music Video. Those data were analyzed based on theory of Gillian Dyer about element visual communication, theory of Semiotics proposed by Ogden & Richard, and theory of meaning by Leech. The result of the analysis found that eleven element visual communications in the Doushite Kimi Wo Suki Ni Natte shimattan Darou and Stand By U Music Video . Relation of verbal and visual signs in those video tell about regret and broken heart of man. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Semiotics, Verbal Sign, Visual Sign